Technology Adoption and Entrepreneurial Leadership as Drivers of Organisational Performance in the Vhembe District, South Africa - Muenda, Mutshidza Kingsley; Ndwamai, Reginald Mulalo; Nkondo, Livhuwani Gladys; Ngirande, Hlanganipai (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: In South Africa’s socio-economically challenged Vhembe District, Limpopo Province, higher education institutions and Small, Medium, and Micro Enterprises (SMMEs) play a critical role in driving innovation, job creation, and regional development. Purpose: This study examines how technology adoption and entrepreneurial leadership jointly function as drivers of organisational performance within the Vhembe District, focusing on High-Performance Computing (HPC) utilisation in higher education and entrepreneurial leadership practices in SMMEs.Design/methodology/approach: This study adopts a comparative synthesis research design using a mixed-methods integrative approach. This study is based on a secondary analysis of two master’s dissertations conducted in the same regional context. The first study investigated factors influencing HPC utilization at the a selected institution using quantitative questionnaires (n = 228) and qualitative interviews (n = 10), analyzed using SPSS and Atlas.ti. The second examined entrepreneurial leadership and SMME performance through qualitative interviews with 20 business owners and analyzed them thematically using Atlas.ti. Cross-domain thematic mapping was employed to identify the convergences, divergences, and synergies between technology adoption and leadership dynamics.Findings/Results: The findings indicate that organizational support, perceived usefulness, and perceived ease of use significantly influence HPC utilization in higher education, while transformational and collaborative entrepreneurial leadership styles strongly enhance SMME performance. Shared challenges across both domains include resistance to change and resource constraints, whereas domain-specific barriers relate to infrastructural limitations in higher education and to market volatility in SMMEs. Conclusion: Technology adoption and entrepreneurial leadership operate as interdependent and mutually reinforcing mechanisms for enhancing organisational performance in resource-constrained environments. Integrated strategies that combine targeted training, infrastructural support, leadership development, and university–SMME collaboration are essential for fostering innovation, sustainability, and socioeconomic development in the Vhembe District.Originality/value (State of the art): This study contributes original value by offering an integrated, context-specific synthesis of technology adoption and entrepreneurial leadership in a shared rural setting. Unlike prior studies that examine these constructs independently, this study demonstrates how their alignment can jointly drive organizational performance in underdeveloped regions.Keywords: entrepreneurial leadership, high-performance computing (hpc), smme performance, technology adoption, Vhembe District